Oral changes after bariatric surgery (Research, Society and Development, 2024)
Bariatric surgery is a procedure that aims to reduce the capacity of the stomach in order to improve the quality of life of obese people, however this type of procedure can lead to changes in the oral cavity. This article aimed to collect data on the main oral changes present in patients who underwent bariatric surgery, in order to demonstrate the importance of multidisciplinary work that includes dental surgeons in the treatment of these individuals. An online questionnaire with objective questions was used on a sample of 51 participants from various locations in Brazil. Of these, 64.7% said they did not have xerostomia and 43.1% said they did not eat a lot of sugar, while 41.2% said they had a diet rich in sugar in the past, which is no longer the case and 15.7% reported excessive sugar intake. The results of this work demonstrated that the bariatric patients approached do not have many post-surgery oral changes, which may be related to low sugar intake and a good frequency of brushing, in addition to the time elapsed since surgery, taking into account that the Most were not advised to look for a professional to take care of their oral health. It is necessary to include dental surgeons in the multidisciplinary team for bariatric patients to provide guidance on oral changes and what to do to minimize them.